On drug-base incompatibilities during extrudate manufacture and fused deposition 3D printing. Issue 1 (January 2017) - Davies, Michael J; Costley, Emily; Ren, James; Gibbons, Paul; Kondor, Anett; Naderi, Majid
Aim: 3D printing can be applied for point-of-care personalized treatment. This study aimed to determine the manufacturability and characteristics of 3D printed, drug-loaded implants for alcohol misuse.Materials & methods: Disulfiram was the drug substance used and polylactic acid (PLA) the base material. Implantable devices were designed in silico . Drug and PLA were placed into the extruder to produce a 5% blend at 1.75-mm diameter. Material characterization included differential scanning calorimetry, thermogravimetric analysis plus inverse GC-surface energy analyzer.Results: Implantable constructs from the PLA feedstock were acquired. The extrusion processes had a detrimental effect on the active pharmaceutical ingredient-base blend. differential scanning calorimetry and thermogravimetric analysis analysis indicated drug–base interactions. Thermal history was found to influence inverse GC probe interaction.Conclusion: Drug-base incompatibilities must be considered during 3D printing.